Hydroids of the genus Sertularella (Cnidaria: Hydrozoa: Sertulariidae) from the Pacific coast of Canada in the collection of the Royal Ontario Museum, with descriptions of four new species - Choong, Henry H. C. (Zootaxa, 2015)
Examination of the hydroid fauna of the Canadian Pacific coast in the collections of the Royal Ontario Museum collected between 1934 and 1985 indicates that the genus Sertularella Gray, 1848 from the infralittoral zone in the region remains poorly enumerated. The present study shows that several European or northeast Atlantic hydroid species, Sertularella conica Allman, 1877, Sertularella rugosa (Linnaeus, 1758), Sertularella tenella Alder, 1856, Sertularella polyzonias (Linnaeus, 1758), and Sertularella fusiformis (Hincks, 1861) have been incorrectly reported from the west coast of North America and suggests that assumptions of cosmopolitanism of some species require verification by continuing refinement of regional species-level taxonomy. Four new species, Sertularella cervicula, S. coronata, S. sacciformis, and S. pacifica are recognized and described in this paper. Sertularella gigantea Hincks, 1874 is recognized for the first time from the Pacific coast of North America.